Bombsites, Adventure Playgrounds and the Reconstruction of London: Playing with Urban Space in Hue and Cry. (2nd January 2019) - Glasheen, Lucie
Abstract : The 1946 Ealing film Hue and Cry is famous for its extensive shots of children playing among bombsites filmed on location in London. Following the film's release a number of people, led by Lady Allen of Hurtwood, advocated turning city bombsites into adventure playgrounds. Yet the relationship between how the film and adventure playground literature imagined the reconstruction of London has not been properly explored. This article uses close reading of Hue and Cry to investigate the meanings that play and the bombsite have within the film. It frames this analysis by use of adventure playground archives, printed pamphlets and books. In doing so it demonstrates that the film sits within a set of responses to bombsite play that reimagined the role of the child in rebuilding London. It argues that Hue and Cry was unique in representing children's play in bombsites as enabling them to reshape space and society.